Analisis Yuridis Terhadap Putusan Hakim Mengenai Putusan Lepas Dari Segala Tuntutan Hukum (Studi Putusan Pengadilan Negeri Mandailing Natal Nomor 26/PID/2019/PN.Mdl) - Cecep Priyayi; Madiasa Ablisar; Mahmud Mulyadi; Sutiarnoto Sutiarnoto (Iuris Studia: Jurnal Kajian Hukum, 2021)
A judicial process ends with a final verdict (vonnis). The decision imposed by the judge must be in accordance with justice and legal certainty. The legal certainty itself lies on the regulations. The Indonesian Penal Code included three possibilities of jurisprudenceon Section 1 Point 11, which is in the form of adjudgment, free, or off from all legal proceedings. In the case of a decision offfrom all legal proceedings, it should be imposed by the judge if all elements of the act against the criminal law are proven, that a criminal act has occurred. However, the perpetrator, apparently, cannot be responsible (does not own a fault in a broad sense) due to certain reasons attached to the defendant as an excuse for forgiveness. The judge should have relied on evidence to prove a verdict. Accordingly, it is necessary to realize that the evidence proposedmust support confidence and be able to strengthen the judge’s stance. Otherwise, the judge shall set him free, if it is not convincing or causing doubts. But if the judge mistakenly free the guilty, then he is only going to deal with juridical accountability due to a fault of applying the law. Based on the background, then the research problem in this study were: (1) How is the legal settingagainst the criminal act of letterforgery; (2) How is the legal setting of judge’sdecision in herziene inlands reglement (HIR), the book of the law of criminal procedure(Code of Criminal Procedure) and bill of book of the law of criminal procedure (Bill of Code of Criminal Procedure); and (3) How is the analysis of the free verdict from any lawsuits, a verdict of District Court Mandailing Natal No.26/pid/2019/Pn.Mdl.The methods applied in this study was normative legal research. The nature of this study was analyticaldescriptive with legislation approach (statute approach).In normative legal research, the data used were secondary data which were obtained by conducting research on the primary, secondary,and tertiary legalmaterials. The juridical analysis of the judge's decision off from all legal proceedingsin District Court Mandailing Natal No. 26/pid/2019/Pn.Mdl, the defendant was proven to have committed the accused but not a criminal act.Based on the judge's decision and after being juridically analyzed, it can be seen that there was an error in the judge's decision, this was due to the absence of some special reasons or forgiveness in the defendant. Therefore, the judge should have decided that the defendant was found guilty of a criminal act and served his sentence in accordance with the final decision (judge's verdict).